2015
DOI: 10.1093/cvr/cvv171
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with remote ischaemic conditioning and insulin or exenatide enhances infarct size limitation in pigs

Abstract: GIK and exenatide activate cardioprotective pathways different from those of RIC, and have additive effects with RIC on infarct size reduction in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…For example, it has been suggested that propofol interferes with the development of RIC, 51 , 52 and it has been implicated as a potential reason for the apparent lack of translation of RIC 53 . Interestingly, we observed studies where propofol (together with either opioid analgesia ± pancuronium) was administered to have effect sizes above the mean 54 , 55 …”
Section: Discussionmentioning
confidence: 82%
“…For example, it has been suggested that propofol interferes with the development of RIC, 51 , 52 and it has been implicated as a potential reason for the apparent lack of translation of RIC 53 . Interestingly, we observed studies where propofol (together with either opioid analgesia ± pancuronium) was administered to have effect sizes above the mean 54 , 55 …”
Section: Discussionmentioning
confidence: 82%
“…Alburquerque-Béjar et al . 130 found an additional 26% reduction in MI size when combining RIC with insulin-like therapies (such as GIK and exenatide) in a porcine acute MI model. The COMBinAtion Therapy in Myocardial Infarction (COMBAT-MI) study (NCT02404376) will investigate the potential benefits of combined reperfusion therapy using RIC with exenatide on MI size reduction in STEMI patients treated by PPCI.…”
Section: Optimizing Approaches To Cardioprotectionmentioning
confidence: 90%
“…Firstly, spectra were digitized in 1000 bins of equal length so that all peaks in the spectra were taken into account. Once digitized, the spectra were fed into software package (SIMCA; Umetrics, Umea, Sweden) where unsupervised principal component analysis (PCA) and supervised orthogonal partial least squares discriminant analysis (OPLS‐DA) analysis were performed in order to discriminate between the groups …”
Section: Methodsmentioning
confidence: 99%